Rape, Popular Culture, and Nirbhaya: A Study of India's Daughter and Delhi Crime - Rajan, Benson; Kundu, Devaleena; Sarkar, Sahana (The Journal of communication inquiry, 2025)
The brutal gang rape of Jyoti Singh (Nirbhaya) on a bus in New Delhi became worldwide news in 2012. Widely known as the Nirbhaya rape incident, it was a landmark case that led the Indian government to amend existing criminal laws on sexual violence and rape. The rape also came to transform the media landscape into a space of social activism. Despite that popular cultural representations of the incident have been critiqued for appropriating rape myths. Through a thematic analysis of the BBC documentary, India's Daughter (2015), and the Netflix series, Delhi Crime (2019), the paper examines the ways in which popular culture sustains and furthers rape culture. By interrogating the thematic-cum-visual discourse of these texts, this paper explores the ideological and sexual tropes to understand the cultural configuration of rape and rape victims/survivors. The study finds the ongoing discourse centering rape in popular culture to be a reiteration of the patriarchal norms prevalent in Indian society.